A look at European buckling curves for aluminium members. Issue 2 (12th March 2019) - Misiek, Thomas; Norlin, Bert; Höglund, Torsten
Abstract: Numerical investigations of compression members made of aluminium are presented and recommendations for reorganizing the buckling classes and curves are derived from these. Finally, the curves are compared with test results.